Analysis of Nursing Care for the Elderly Using Benson Relaxation Therapy to Lower Blood Pressure - Mifta Rilli Adzkia Adzkia; Siska Mayang Sari; Abdurrahman Hamid; Yumiati (Journal of Health Empowerment and Interprofessional Practice, 2026)
Hypertension is a condition in which a person experiences an increase in systolic and diastolic blood pressure beyond normal limits. One of the main problems with hypertension is the increase in blood pressure. In Indonesia, the prevalence of hypertension reaches 25%, increasing sharply in the elderly: 45.3% (45-54 years), 55.2% (55-64 years), 63.2% (65-74 years), and 69.5% (75+ years). In 2024, at the Khusnul Khotimah Social Services Unit, out of 90 elderly people, 46 people experienced hypertension as the number one disease. Non-pharmacological blood pressure management can be done by applying Benson relaxation therapy. This scientific paper aims to analyze nursing care for Mrs. N and Mr. H and evaluate the application of Benson relaxation therapy in reducing blood pressure in elderly people with hypertension at the Husnul Khotimah Social Services Unit, Riau Province Social Services correctly, appropriately and in accordance with professional nursing standards. This application uses a one-group pretest-posttest design with 2 subjects. The research instrument uses an observation sheet. The intervention was administered from November 29 to December 1, 2025. This intervention was carried out for 15 minutes for 3 consecutive days, morning and afternoon. The results of blood pressure for 3 days with an average systolic value before therapy was 148.75 and a diastolic value of 94.17 after therapy, the average systolic value was 144.33 and a diastolic value of 90.75. Meanwhile, the average decrease in blood pressure for 3 days was a systolic of 4.42 and a diastolic of 3.42. The results of Benson relaxation therapy have been proven to reduce blood pressure. It is hoped that this scientific paper report can be used as a guide in providing nursing care, especially the application of Benson relaxation interventions.